Réflexion pour une approche critique de la notion de droit à l'information en droit international - Trudel, Pierre (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1982)
Despite the fact that the right to information implies concomitant duties upon the information media, the dominiant opinion in international law is that this notion is synonymous with the well-known concept of « freedom of information ». There appears to be a large consensus among all nations that the right to information is indeed a reformulation of the concept of freedom of information. However, despite some guarantees resulting from the Helsinki Agreements, attemps to specify the exact content of the notion of freedom of information have been unsuccessful at the international level.